Oxygen minimum zone variations in the tropical Pacific during the Holocene. Issue 20 (24th October 2015) - Xu, Xu; Segschneider, Joachim; Schneider, Birgit; Park, Wonsun; Latif, Mojib
Abstract: We performed simulations with a global model of ocean biogeochemistry forced with orbitally driven anomalies of oceanic conditions for the mid‐Holocene, known as Holocene climate optimum, to investigate natural variability in the eastern equatorial Pacific oxygen minimum zone (EEP OMZ). While the global mean temperature during the mid‐Holocene was likely slightly higher than the 1961–1990 mean, the sea surface temperature in the EEP was slightly lower. Mid‐Holocene oxygen concentrations in the EEP OMZ are generally increased, locally by up to 50%, and the EEP OMZ volume was, depending on definition of the OMZ threshold, at least 6% lower. These higher oxygen levels are the combined result of competing physical and biogeochemical processes. Our results imply that mechanisms for past changes in the EEP OMZ intensity and extension can differ from the global warming driven decline in oxygen levels observed for the recent decades and predicted for the future. Key Points: Eastern equatorial Pacific was less oxygen depleted during mid‐Holocene despite warmer climate Orbitally driven mid‐Holocene climate changes impact on ocean biogeochemistry Ocean physics dominate over ecology in driving mid‐Holocene OMZ variability